PRAKTEK PROSTITUSI DAN PENGARUH TREND KUNJUNGAN WISATAWAN MANCA NEGARA DI KOTA YOGYAKARTA - Erlangga Brahmanto (LPPM Universitas Bina Sarana Informatika, 2015)
ABSTRACT Tourism in addition to having a positive impact in the economy also has a negative impact on socialculture . The development of tourism is directed into one of the country 's foreign exchange to support development activities likely to lead to a progressive economic aspect , cultural aspect , whichpressure due to the shift in immigrant communities are less concerned about socialcultural environment . Yogyakarta is very rapid progression from year to year . prostitution in the city of Yogyakarta is also experiencing significant growth . This is as a consequence of the results of the development of tourism in Yogyakarta . Sarkem region , Babarsari , Parangkusumo beach is a picture of the author wants to lift to the research topic entitled